The sexual objectification of girls and aggression towards them in gang and non-gang affiliated youth. Issue 5 (28th May 2017) - Vasquez, Eduardo A.; Osinnowo, Kolawole; Pina, Afroditi; Ball, Louisa; Bell, Cheyra
ABSTRACT: Sexual objectification is related to various negative attitudes and outcomes, including rape proclivity and reduced moral concern for the objectified, which suggests that objectification has implications for aggression. Our study examined the relationship between objectification and general aggressive behaviour in adolescents, including gang-affiliated youth. We hypothesized that (1) objectification would correlate with aggression towards girls, (2) gang affiliation would correlate with objectification and aggression towards girls, and (3) objectification and gang affiliation would interact such that strongly affiliated participants who objectified girls would be most aggressive towards them. We also hypothesized that sexual objectification would be a significant predictor of aggression above and beyond other factors, such as trait aggression. As predicted, objectification correlated with aggression towards girls and with gang affiliation, which also correlated with aggression. In addition, objectification predicted aggression towards girls, after controlling for other relevant factors. Further, we found an objectification × gang affiliation interaction, which differed from our original predictions. Among participants low in gang affiliation, objectification of girls predicted levels of aggression towards them. Among those high in gang affiliation, however, objectification did not predict aggression. We discussed the implications of our findings for general aggression.